Biometría de Bufo marinus (Anura: Bufonidae) del refugio nacional de vida silvestre Golfito, Costa Rica (ING) - Cabrera Peña, Jorge (1995)
Biometrical analysis of Bufo marinus was carried out in the Golfito National Wildlife Refuge, Golfito, Puntarenas, Costa Rica, between May 1986 and June 1987. Statistical analysis of biometrical parameters indicated that this species has sexual dimorphism and females had greater size and weight.